Conceptual Design of a Semi-Automatic Process Line for Recycling Photovoltaic Panels as a Way to Ecological Sustainable Production - Niekurzak, Mariusz; Lewicki, Wojciech; Coban, Hasan Huseyin; Brelik, Agnieszka (Sustainability, 2023)
The article presents the developed technology for the comprehensive recycling of depleted, used or damaged photovoltaic (PV) cells made of crystalline silicon. The developed concepts of technology and the results of research on recycling were presented on silicon photovoltaic cells and modules. The sequence of steps and the type of procedures used are proposed. A thermal delamination method for used commercial photovoltaic modules has been developed to separate the materials. In addition, a recycling line was proposed along with the selection of machines and a holistic approach to project profitability based on a SWOT analysis. The presented semi-automatic installation enables recycling on a laboratory scale. The line was designed for the assumed capacity of 30 t/h. The total energy demand for the designed line was calculated, which showed that 16.49 kWh is needed to recycle 1 ton of photovoltaic laminates. Implementation of developed solutions on an industrial scale will allow to reduce production costs, mainly thanks to energy savings, which translates into less devastation of the natural environment and reduced material consumption. In addition, the implementation of the PV module recycling system will reduce and, consequently, eliminate a significant amount of used PV devices deposited in landfills. The content of the article gives a fresh and innovative look at the essence of photovoltaic panel recycling processes in terms of production benefits as well as financial and environmental benefits.